PENGARUH KOMPETENSI SUPERVISI DAN MANAJERIAL KEPALA MADRASAH TERHADAP MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH SE-KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Nurhayati Nurhayati; Arifuddin Siraj; Muhammad Yaumi (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study attempts to describe supervision competence and managerial competence of the heads schools, to describe educational quality of Islamic Junior High Schools (MTS), and then to analyze the influence of the supervision competence and managerial competence toward educational quality of MTS both partially and simultaneously in Gantarang District, Bulukumba Regency. This study is ex-post facto. The population is all the teachers of all private MTS with accredited A. It is analyzed all the teachers as the sample with 54 people of all. Method of data collection is through questionnaires about supervision competence, also using data analysis, and multiple regressions. The results of the study obtained that the supervision competence and the managerial competence of the head is in the medium category. The supervision competence of the head schools significantly influences the quality of education. The managerial competence of the head schools significantly influences the quality of education. Both supervision competence and managerial competence of the heads of schools have the significantly influencer toward educational quality of MTS, in Gantarang district, Bulukumba Regency.